Internal ocean‐atmosphere variability drives megadroughts in Western North America. Issue 18 (29th September 2016) - Coats, S.; Smerdon, J. E.; Cook, B. I.; Seager, R.; Cook, E. R.; Anchukaitis, K. J.
Abstract: Multidecadal droughts that occurred during the Medieval Climate Anomaly represent an important target for validating the ability of climate models to adequately characterize drought risk over the near‐term future. A prominent hypothesis is that these megadroughts were driven by a centuries‐long radiatively forced shift in the mean state of the tropical Pacific Ocean. Here we use a novel combination of spatiotemporal tree ring reconstructions of Northern Hemisphere hydroclimate to infer the atmosphere‐ocean dynamics that coincide with megadroughts over the American West and find that these features are consistently associated with 10–30 year periods of frequent cold El Niño–Southern Oscillation conditions and not a centuries‐long shift in the mean of the tropical Pacific Ocean. These results suggest an important role for internal variability in driving past megadroughts. State‐of‐the‐art climate models from the Coupled Model Intercomparison Project Phase 5, however, do not simulate a consistent association between megadroughts and internal variability of the tropical Pacific Ocean, with implications for our confidence in megadrought risk projections. Key Points: Megadroughts are consistently driven by the tropical Pacific The tropical Pacific conditions underlying megadroughts are consistent with internal variability Models also simulate megadroughts driven by internal variability, but not consistently the tropical Pacific